IMPLEMENTATION OF HAND MASSAGE ON REDUCING ANXIETY IN ELDERLY PEOPLE WITH HYPERTENSION: IMPLEMENTASI HAND MASSAGE TERHADAP PENURUNAN KECEMASAN PADA LANSIA PENDERITA HIPERTENSI - Miftaqul Bilka Subiantoro; Fatma Ardian Sari; Betty Shinta Damayanti; Devie Mutiara Hati; Gessa Tegar Syahrul Mauluddin; Sovea Choirun Nisya’; Trijati Puspita Lestari; Moh. Saifudin (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Hand massage is a massage technique on the hands that is done to relax the mind and reduce or eliminate pain. Anxiety is a person's condition caused by several factors, so that it can cause fear and worry. Objective: This activity aims to know the effectiveness of hand massage on reducing anxiety in elderly people with hypertension. Method: Community service includes 1) Pre test; 2) implementation of activities; 3) Post test. The method used is a combination of counseling using poster media and demonstration of hand massage to people with hypertension. This activity was carried out on May 16, 2024 at the Mental Love Nursing Home located in Turi Village, Turi District, Lamongan Regency, with 27 elderly people. Results: There was a significant reduction in anxiety and blood pressure levels in the elderly after hand massage. Conclusion: This activity has a significant positive impact on the physical and mental health of elderly people with hypertension. The hand massage techniques provided are anticipated to be utilized by the elderly in various nursing homes or senior communities, hence extending their benefits